PENGARUH PENDEKATAN BERMAIN SIRKUIT TERHADAP HASIL BELAJAR DRIBBLING SEPAK BOLA PADA SISWI SMP - Rahman, Aulia; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractAs the problem of this research is there have influences of circuit play approach in learning of dribbling soccer of student at class VIII SMP Negeri 3 Sungai Raya?. The purpose of this study is to determine the effect of circuit play approach in learning dribbling soccer to schoolgirls syudent in SMP Negeri 3 Sungai Raya. The population of this research is class VIII there are counted 8 classes, which class amounted to 121 students. Technique of sampling in this research is using purposive sampling technique, which are 66 students as an experimental class. The method is this research is used experiment research with pre-experimental design. The data analysis was done by computerization and analysis by using t-test. Based on the result of t-test in experimental class, p value 0,000 <0,05 then Ho is rejected (Ha accepted) means that there are had influences of playing circuit approach to the learning result of dribbling soccer on garde VIII students of SMP Negeri 3 Sungai Raya,with the value among pre-test and post-test is 24.56. Keywords: Playing, Learning Outcomes, Dribbling.